Recent recycling procedures for end-of-life Vehicles (ELV) metals in Malaysia - Muhammad Khairulamiri Zamri,; Nizaroyani Saibani,; Mohd Nizam Ab Rahman,; Norngainy Mohd Tawil,; Siti Maisarah Mohd Pisal,; Rosni Tarmid,; Hawa Hishamuddin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
In Malaysia, a large number of abandoned End-of-Life Vehicles (ELV) problems pose a concern due to a lack of adequate regulation and action, while in Japan, a recycling system has been built and legislation controlling ELV recycling has been approved. The purpose of this article was to identify and investigate the current ELV recycling procedures in Malaysia, with a focus on metal recovery. This research also attempted to identify and review the ELV metal recycling procedures in Japan, as well as to compare and contrast them with Malaysian practices. A case study was conducted to investigate the ELV metal recycling procedure used by recyclers in Malaysia, thereby producing an ELV recycling framework. Publications on ELV metal recycling from Malaysia, and Japan will assist in determining, by identifying the ELV metal recycling technique used, the disparity between these two countries. Japan’s ELV recycling has long been recognized for its importance in secondary metal recovery and reducing ELV waste to the environment. The recovery of secondary resources, such as ferrous metals, non-ferrous metals, and precious metals, from the recycling of ELVs reduces reliance on primary resources. It has been proven that ELV recycling aids in the prevention and control of ELV development around the world.